The Role of Madrasah Principal Leadership and Work Environment as Determinants of Teacher Performance - Nada Afifah zahru; Suparta Rasyid; Nasir Usman (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Teachers’ performance at Madrasah Ibtidaiyah Negeri (MIN) in Aceh Barat Daya remains suboptimal, shows by low discipline, monotonous teaching practices, limited use of technology, inadequate supporting facilities, and an unconducive work environment. This condition is suspected to be influenced by the ineffective leadership of the madrasah principal and a less supportive work environment. This study aims to analyze the influence of the principal’s leadership and the work environment on teachers’ performance, both partially and simultaneously. A quantitative approach with an explanatory research method was employed. The research population consisted of all teachers from five MINs in Aceh Barat Daya, with a sample of 103 teachers selected using a random sampling technique. Data were collected through questionnaires and documentation, and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS version 4 software. The results revealed that the principal’s leadership had a positive and significant effect on teachers’ performance, with a path coefficient of 0.313. The work environment also had a positive and significant effect, with a path coefficient of 0.560. Simultaneously, the two variables contributed 64.1% to the improvement of teachers’ performance, while remaining percentage was influenced by other factors outside the scope of this study. Effective, participatory, and communicative leadership, along with a comfortable and harmonious work environment, are key factors in enhancing teachers’ professionalism, creativity, and productivity in the madrasah. These findings are expected to serve as a reference for schools and policymakers in designing strategies to improve the quality of learning